2020
DOI: 10.1306/10031919011
|View full text |Cite
|
Sign up to set email alerts
|

Slip sliding away: Enigma of large sandy blocks within a gas-bearing mass transport deposit, offshore northwestern Greenland

Abstract: The northwestern Greenland margin contains several underexplored sedimentary basins formed by Cretaceous rifting and Cenozoic postrift sedimentation. The basins are thought to contain significant hydrocarbon reserves, although no exploration wells have been drilled to date. This paper reports the discovery of a gas-charged submarine landslide mass transport deposit (MTD) covering 420 km 2 (162 mi 2 ) above the Melville Bay ridge (MBR) rift structure. The sedimentary succession that deformed into the MTD was li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…These features are interpreted as MSGLs due to their morphology (Spagnolo et al, 2014) and similarity to MSGLs observed on the local seafloor and buried on other glaciated margins (e.g. Andreassen et al, 2007;Dowdeswell et al, 2006;Montelli et al, 2017;Rea et al, 2018).…”
Section: Subglacial Landformsmentioning
confidence: 87%
See 1 more Smart Citation
“…These features are interpreted as MSGLs due to their morphology (Spagnolo et al, 2014) and similarity to MSGLs observed on the local seafloor and buried on other glaciated margins (e.g. Andreassen et al, 2007;Dowdeswell et al, 2006;Montelli et al, 2017;Rea et al, 2018).…”
Section: Subglacial Landformsmentioning
confidence: 87%
“…Switches in ice stream pathways on continental shelves between different glacial maxima have been observed on the mid-Norwegian margin, where new cross-shelf troughs were formed through the erosive action of ice (Dowdeswell et al, 2006). In contrast to the mid-Norwegian margin, the available data in Melville Bugt do not show evidence of buried cross-shelf troughs.…”
Section: Palaeo-ice Streamsmentioning
confidence: 99%
“…A shallow coring program was carried out in 2012, but no exploration wells have been drilled. Since then, the identification of a large potential gas reservoir (Cox et al, 2020a) and widespread evidence for shallow gas and gas hydrates (Cox et al, 2020b) further support an active petroleum system, thus underscoring the need for a geohazard assessment study prior to drilling.…”
Section: Regional Geohazard Considerationsmentioning
confidence: 99%
“…This included the physical character of anomalies, which were often isolated bright spots or brightening along single horizons ( Fig. 8), as well as their spatial and stratigraphic distribution, which was widespread within all levels of the post-rift stratigraphy (mu-D to -A) and focussed around the Melville Bay Ridge (Cox et al, 2020b). The seismic amplitude range of the bright anomalies was also analysed to aid amplitude extractions.…”
Section: Shallow Gas Detectionmentioning
confidence: 99%
See 1 more Smart Citation